2023
DOI: 10.1021/acs.inorgchem.3c00140
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Two-Dimensional Tetrathiafulvalene-Copper Metal–Organic Framework with Boosted Electrochemical Performances for Supercapatteries

Abstract: Metal–organic frameworks (MOFs) have attracted noticeable attention as promising candidates for electrochemical energy storage. However, the lack of electrical conductivity and the weak stability of most MOFs result in poor electrochemical performances. Here, a tetrathiafulvalene (TTF)-based complex, formulated as [(CuCN)2(TTF(py)4)] (1) (TTF-(py)4 = tetra(4-pyridyl)-TTF), is assembled by in situ generation of coordinated CN– from a nontoxic source. Single-crystal X-ray diffraction analysis reveals that compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…47 Recently, Zhu et al have reported a CuCN-based MOF as an electrode material for a supercapattery with a specic capacity of 677.5 C g −1 at 1 A g −1 current density. 48 In the continuation of research involving the design and synthesis of these interesting MOFs, herein, we report on the synthesis of a new 2D copper(I) cyanide-based semiconductive MOF using a 1H-1,2,4-triazole substituted pyridine ligand as a linker. The superior conductivity and the presence of Cu(I) redox-active centers in its 2D structure, which eventually transform into an interesting 3D-framework with suitable channel structure due to p-p stacking, encouraged us to investigate it as a binder and conducting additive-free electrode material in energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Recently, Zhu et al have reported a CuCN-based MOF as an electrode material for a supercapattery with a specic capacity of 677.5 C g −1 at 1 A g −1 current density. 48 In the continuation of research involving the design and synthesis of these interesting MOFs, herein, we report on the synthesis of a new 2D copper(I) cyanide-based semiconductive MOF using a 1H-1,2,4-triazole substituted pyridine ligand as a linker. The superior conductivity and the presence of Cu(I) redox-active centers in its 2D structure, which eventually transform into an interesting 3D-framework with suitable channel structure due to p-p stacking, encouraged us to investigate it as a binder and conducting additive-free electrode material in energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…47 Recently, Zhu et al have reported a CuCN-based MOF as an electrode material for a supercapattery with a specific capacity of 677.5 C g −1 at 1 A g −1 current density. 48…”
Section: Introductionmentioning
confidence: 99%